Pensare “con” la tecnica: La nozione di individuo nella filosofia di Gilbert Simondon - Macrì, Saverio (Bollettino Filosofico, 2023)
This paper examines the contribution of technological thought in Gilbert Simondon’s philosophy of individuation. Simondon’s merit consists in having rethought the traditional theme of individuality, refuting the ontological primacy of the category of substance in favor of a theory of relations. What distinguishes the originality of the French thinker is the fact that this speculative system is nourished by his research in the field of technology. Indeed, he draws from the information theory a model to illustrate the processes of individuation, from the physical to the vital level, from the psychic to the collective. Terms and concepts belonging to the field of technology – such as amplification, communication, modulation, relay, and transduction – are thus redefined to describe the relational character of the individual. Keywords: Individuation, Information, Interactivity, Relation, Technology